OPTIMALISASI MANAJEMEN PEMBIAYAAN UNTUK KEBERLANJUTAN PERGURUAN TINGGI ISLAM - Arifin, Misbahul (Al Hikmah: Jurnal Tarbiyah dan Ilmu Keguruan, 2025)
This study focuses on the optimization of financial management to support the sustainability of Islamic higher education institutions, which face complex challenges related to limited funding, weak innovation, and the lack of integration of sharia principles in financial governance. The purpose of this research is to identify financing strategies that are relevant, adaptive, and aligned with Islamic values, enabling universities to maintain both financial stability and legitimacy. The method employed is a literature review, analyzing recent publications from international and national journals between 2020–2025 that are relevant to the research theme. The findings reveal that the sustainability of Islamic higher education can be achieved through multidimensional strategies, including diversification of funding sources, utilization of Islamic philanthropic funds, financial digitalization, sharia-based governance, and collaboration with industry. The implications highlight the need for a holistic financial management model that emphasizes not only financial efficiency but also sharia compliance and adaptability to global dynamics.